5 - Institutional Design and the Implementation of the African Peace Security Architecture in Eastern Africa - Rwengabo, Sabastiano (Africa Development, 2021)
The relationship between, on the one hand, the design of the African Peace Security Architecture (APSA), and implementation of APSA’s institutional provisions, on the other, remains less well understood, contrary to scholarly optimism on the future of security cooperation in Africa. For instance, security cooperation in Eastern Africa portrays interlocked but dissimilar institutional features that impact APSA’s implementation: some features apply only to the EAC; others encompass non-East African Community (EAC) states under the Eastern Africa Standby Force; still others interlock the Great Lakes Region with Inter-Governmental Authority on Development (IGAD) and beyond. Drawing upon field work on security cooperation in the EAC, existing studies and documents on APSA, this article analyses how institutional design affects APSA’s implementation in Eastern Africa. Three design aspects are considered decision- making rules; the bindingness of security commitments; and implementation mechanisms. The findings indicate that states’ overlapping memberships in both Regional Economic Communities (RECs) and Regional Brigades stretching beyond these RECs breeds decision-making overlaps, conflicting obligations, and parallel conventions with different levels of force in terms of how binding to states these instruments are. Overlapping membership also engenders implementation challenges when member States are overstretched. APSA’s future, The article argues, lies in reconstituting and tailoring Regional Brigades along RECs, and enhancing RECs’ politico-security cooperation in order to reduce conflicting decisions, enhance intra-REC coordination and commitment, and augment confidence-building measures among REC member-States.